Ammoniacal Nitrogen Removal Using flamboyant pods ( Delonix Regia) Adsorbent for Natural Rubber Wastewater Treatment - Daud, Zawawi; Ahmad, Baharin; Awang, Halizah; Abubakar, Mahmoud Hijab; Nasir, Nazlizan; Tajarudin, Husnul Azan (International Journal of Integrated Engineering, 2019)
Plant waste such as Delonix Regia Pods (DRP) have the potential to be used as adsorbents. A study of lignocellulose delonix regia pods was carried to assess ammoniacal nitrogen removal from natural rubber wastewater. Sample wastewater was taken from the rubber processing industry and characterization was carried out. Outcomes from the analysis shows that the ammoniacal nitrogen concentration was 66 mg/L and higher than the recommended wastewater discharge standards. Batch experiments were conducted on the effect of dose, pH, shaking speed and contact time parameters for optimum condition. The results revealed that the optimal dosage, pH, shaking speed and contact time is 4.5 g, pH 8, 150 rpm and 120 minutes with ammoniacal nitrogen removal efficiency of 74.3 % and the adsorption capacity of 1.22 mg/g. Pseudo second order kinetic model was found to fit the data better and the R2 obtained was 0.9992. From the study, it can be concluded that the media can be used for the removal of ammoniacal nitrogen in natural rubber wastewater and subsequently reduce environmental pollution. Hence, it can be sustainable and environmentally friendly.